2019
DOI: 10.1158/1538-7445.am2019-ct042
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT042: Fecal microbiota transplantation (FMT) and re-induction of anti-PD-1 therapy in refractory metastatic melanoma patients - preliminary results from a phase I clinical trial (NCT03353402)

Abstract: Background: The majority of metastatic melanoma patients treated with Programed cell Death (PD)-1 blockade fail to achieve durable response. The gut microbiota profoundly affects host immunity, and fecal microbiota transplantations (FMT), which transfers the entire gut microbiota from one host to another, has been shown to enhance anti-PD-1 effectiveness in murine models. We report initial safety and efficacy results from the first three patients treated on a Phase I study of FMT and re-induction anti-PD-1 the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In NSCLC and melanoma, faecal microbiota transplant (FMT) from human ICI responders improved response to ICI in mice, raising a possibility of a microbiome based therapeutic intervention (91, 92). A pilot study that subjected three ICIrefractory melanoma patients to FMT from ICI-responders has reported preliminary results (103). FMT increased intratumoural CD8 + TILs in recipients, and this translated into a clinical and radiological response in two of three patients.…”
Section: The Gut and Tumour Microbiomementioning
confidence: 99%
“…In NSCLC and melanoma, faecal microbiota transplant (FMT) from human ICI responders improved response to ICI in mice, raising a possibility of a microbiome based therapeutic intervention (91, 92). A pilot study that subjected three ICIrefractory melanoma patients to FMT from ICI-responders has reported preliminary results (103). FMT increased intratumoural CD8 + TILs in recipients, and this translated into a clinical and radiological response in two of three patients.…”
Section: The Gut and Tumour Microbiomementioning
confidence: 99%
“…FMT is effective for treating recurrent Clostridioides difficile infection (rCDI) (van Nood et al 2013), but is also under investigation for the treatment of ulcerative colitis (UC), Crohn's disease (CD), liver diseases, obesity and metabolic disease, food allergy, graft-versus-host disease, check point colitis and to improve the efficacy of cancer immunotherapy (Ooijevaar et al 2019;Wang et al 2018;Baruch et al 2019). Clinical trials of FMT in UC have suggested some potential for using microbiota-targeted therapy in this setting (Paramsothy et al 2017;Moayyedi et al 2015;Rossen et al 2015;Costello et al 2019), but evidence for efficacy in other indications is currently extremely limited and there is currently little or no scientific basis for the adoption of FMT as a mainstream therapeutic option outside of rCDI.…”
Section: Introductionmentioning
confidence: 99%
“…FMT is effective for treating recurrent Clostridioides difficile infection (rCDI) (5), but is also under investigation for the treatment of ulcerative colitis (UC), Crohn's disease (CD), liver diseases, obesity and metabolic disease, food allergy, graft-versushost disease, checkpoint colitis, and to improve the efficacy of cancer immunotherapy (6)(7)(8). Clinical trials of FMT in UC have suggested some potential for using microbiota-targeted therapy in…”
mentioning
confidence: 99%
“…FMT is effective for treating recurrent Clostridioides difficile infection (rCDI) ( 5 ), but is also under investigation for the treatment of ulcerative colitis (UC), Crohn’s disease (CD), liver diseases, obesity and metabolic disease, food allergy, graft-versus-host disease, checkpoint colitis, and to improve the efficacy of cancer immunotherapy ( 6 8 ). Clinical trials of FMT in UC have suggested some potential for using microbiota-targeted therapy in this setting ( 9 12 ), but evidence for efficacy in other indications is currently extremely limited, and there is currently little or no scientific basis for the adoption of FMT as a mainstream therapeutic option outside of rCDI.…”
mentioning
confidence: 99%